(untitled) (Linguostylistic Studies, 2020)
The article clarifies the functional and stylistic parameters of evaluation as a linguistic category, which covers different levels of language units with evaluative semantics and conveys the positive or negative attitude of the speaker to the subject, phenomenon, concept. The scale of positive or negative semantic evaluation is formed in accordance with the established social, national-cultural, and moral values. Logical (rational) and emotional (irrational) assessment in the text interact. Logical evaluation is motivated by the objective thoughts, while emotional – by the feelings of the subject to the object (person, object, phenomenon, event, etc.). Units of logical evaluation are the words and phrases with positive and negative semantics from the intellectual sphere of linguistic thinking, and units of emotional - linguistic means with expressive connotation. Evaluation is provided via the use of language units registered in dictionaries or in the memory of native speakers in terms of their values: good and evil, true and false, justice and injustice, benefit and harm, beauty and ugliness, the allowed and forbidden. Evaluative semantics is revealed in the appropriate contextual conditions, in particular, in updating the structure and semantics of the components or stylistic marking of syntactic units. The combination of logical and emotional evaluation allows for closely related to the communication situation pragmatic evaluation of the text as a whole. In particular, these are verbal acts of approval, encouragement, commitment (plus on the scale of evaluations) or, vice versa, condemnation, contempt (minus on the scale of evaluations), which are based on a joint bank of knowledge and norms of interlocutors. The stylistic potential of evaluation in the text is revealed on lexical, phraseological, and syntactic levels. Texts, differing in style and content, differ in the ways they express verbal axiology.